Surgical treatment of fracture-related infection Part I: Bone and soft tissue debridement - Azi, Matheus Lemos; Valderrama-Molina, Carlos Olivier; Vallejo-Díaz, Alejandro; Días-Belangero, William; Giordano, Vincenzo; Carabelli, Guido; Sancineto, Carlos Federico (Revista Colombiana de Ortopedia y Traumatología, 2024)
Fracture-related infection (FRI) is a severe complication of the surgical treatment of traumatic bone injuries and occurs more frequently in patients with such injuries than in those undergoing elective joint replacement surgery. The surgical treatment of FRI is based on meticulous bone and soft tissue debridement, dead space management, reconstruction of soft tissue defects, and restoration of bone stability in non-union fractures. Furthermore, the use of local antibiotic therapy is recommended in some cases. The objective of this article was to review the current concepts of available techniques for the surgical treatment of FRI, with emphasis on bone and soft tissue debridement.